2016
DOI: 10.3389/fpsyt.2016.00186
|View full text |Cite
|
Sign up to set email alerts
|

What Role Can Avatars Play in e-Mental Health Interventions? Exploring New Models of Client–Therapist Interaction

Abstract: In the burgeoning field of e-mental health interventions, avatars are increasingly being utilized to facilitate online communication between clients and therapists, and among peers. Avatars are digital self-representations, which enable individuals to interact with each other in computer-based virtual environments. In this narrative review, we examine the psychotherapeutic applications of avatars that have been investigated and trialed to date. Five key applications were identified (1) in the formation of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…Feedback suggested that the externalization of internal thoughts, feelings and experiences helped the young people express how they were feeling. Although we are limited in reporting findings from two cases, their experiences align with those from previous research into avatar-based counselling Rehm et al, 2016;van Rijn et al, 2017van Rijn et al, , 2018. A key theme from this research centred around the software allowing young people to express themselves outside of 'just using words all the time' .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Feedback suggested that the externalization of internal thoughts, feelings and experiences helped the young people express how they were feeling. Although we are limited in reporting findings from two cases, their experiences align with those from previous research into avatar-based counselling Rehm et al, 2016;van Rijn et al, 2017van Rijn et al, , 2018. A key theme from this research centred around the software allowing young people to express themselves outside of 'just using words all the time' .…”
Section: Discussionsupporting
confidence: 77%
“…In a qualitative study exploring Swedish CYP's views of community health clinics, CYP expressed preferences for utilizing activities within sessions to help their engagement, communication, and choice to disclose: younger adolescents spoke about using nonverbal ways to express their thoughts and feelings (Persson, Hagquist, & Michelson, ). Digital avatar‐based therapies may provide a creative outlet for expression, akin to play therapy (van Rijn, Cooper, & Chryssafidou, ) and be a medium of communication for the CYP and therapist to share within therapy (Rehm et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Avatar-based technology facilitates several therapy approaches, as it can substitute face-to-face contact with a clinician. According to Rehm et al (2016), two concepts exist of how to include avatars into therapy: On the one hand, the patient interacts with an avatar, this was used as an effective tool in Virtual Reality Exposure Therapy (e.g. Cárdenas and De La Rosa, 2012 for PTSD), and as the embodiment of a real clinician or a supporting tool for self-management technology (e.g., Pinto et al, 2016 for depressive symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…The community interacts in the simulated world using either text-based, 2-D and/or 3-D graphical models called avatars (20). Although underresearched, virtual world platforms have the potential to reduce communication barriers and improve access to support and treatment in people with mental health disorders (21).…”
Section: Introductionmentioning
confidence: 99%
“…One of most widely used virtual world environments is the online and freely available social world Second Life©. Second Life© has been used as a virtual world platform in healthcare education, delivery, and engagement and has considerable potential in delivering psychological therapies (21,22). For example, Second Life© has been used to treat social anxiety and has been found to be feasible and acceptable with effects sizes potentially comparable to face-to-face Cognitive Behavior Therapy (CBT) for Seasonal Affective Disorder (23) and in treating social cognition problems in autism (24).…”
Section: Introductionmentioning
confidence: 99%